Prevalencia de linfocitosis monoclonal de células b y factores asociados: Metaanálisis 2002-2012 (2015)
Introduction: studies on monoclonal B-cell lymphocytosis show wide divergence prevalence and limitations in its internal and external validity since the specificities of the groups studied; the majority of researchers use non-probability sampling and do not explain the bias control. Magnitude by sex and age group has not been analyzed, which do not allow the consolidation of a hypothesis about associated factors. Objective: to estimate the overall and specific prevalence of monoclonal B-cell lymphocytosis for sex and age, 2002-2012. Methods: a meta-analysis search for original investigations published in six databases. The overall and specific prevalence of monoclonal B-cell lymphocytosis was calculated by sex and type of population. Intervals were calculated for the difference in proportions between the prevalence in men and women and in general and sick population and with family history of chronic lymphocytic leukemia. Results: A prevalence of 7, 8 % of monoclonal lymphocytosis was found in a population of 18 527 individuals included in this study and no difference of prevalence in men (8,7 %) and women (7,8 %) was found, while in the comparison of the three analyzed populations the prevalence was statistically higher in patients (24 %), lower in the general population (6,7 %) and in individuals with family history of chronic lymphocytic leukemia (15 %). The prevalence of monoclonal Bcell lymphocytosis was higher in adults over 40 years. Conclusion: the higher prevalence corresponds to individuals underlying base diseases followed by relatives in first degree of patients with chronic lymphocytic leukemia; sex did not represent an associated factor with the presentation of monoclonal B-cell lymphocytosis. © 2015, Editorial Ciencias Medicas. All rights reserved.